THE LEVEL OF CAREER PLANNING OF XI GRADE STUDENTS OF SENIOR HIGH SCHOOL - Aufal Marom; Heri Saptadi Ismanto; Ajeng Dianasari (Universitas Negeri Surabaya, 2024)
Career planning is a very important aspect of student development. This research aims to understand the scale of career planning levels of class XI students at Senior High School of Semarang. The use of this research method applies a quantitative descriptive methodology with a survey research type. There is a total research population, namely class XI of Senior High School of Semarang, totaling 432 students. The researchers used simple random sampling to collect samples, calculated using the Slovin formula, and obtained a total of 208 students. This research applies a career planning scale that has been validated as a data collection tool. Based on the results of the career planning scale analysis, we obtained the percentage results of the level of career planning for class The low category obtained 8.17% with a total of 17 class XI students. From the results of this analysis, it shows that the level of career planning for class XI students at Senior High School Semarang has a medium career planning level scale. This is a success in the career guidance services that guidance and counseling teachers have provided at schools, so that students have good career planning.